Non-Surgical Ayurvedic Management of Hemorrhagic Ovarian Cyst: A Case Report - Kumari, Sunita; Kumar Panda, Jitesh; Tanwar, Suniti (International Research Journal of Ayurveda & Yoga, 2025)
Hormonal balance is essential throughout a woman’s life, from menarche to menopause. Any disruption in the regulation of ovarian hormones, especially involving the hypothalamic-pituitary-ovarian axis, can have a profound impact on a woman’s physical, emotional, and reproductive well-being. Unhealthy dietary habits and modern lifestyle patterns often contribute to hormonal imbalances, increasing the risk of ovarian cyst development. Hemorrhagic ovarian cysts are among the most frequently encountered types in routine gynecological practice. Although many cases resolve on their own without treatment, more severe instances may require surgical intervention. A 17-year-old female visited the outpatient department with symptoms of irregular menstrual cycles associated with lower abdominal pain and weight gain. Ultrasonography (USG) was advised and finding suggested a right-sided hemorrhagic ovarian cyst. She was treated for 3 months using traditional Ayurvedic formulations such as Chitrakagranthikadi Kashayam, Syp Womalyn, and Kanchnar guggulu tablets aimed at reducing symptoms and promoting cyst resolution. Only traditional Ayurvedic medicines were administered throughout the treatment period. Follow-up USG revealed complete resolution of the cyst, along with significant improvement in the patient’s symptoms. Although most hemorrhagic ovarian cysts resolve on their own, the supportive role of Ayurveda in symptom management and cyst resolution as seen in this case suggests that it can serve as a viable, non-invasive alternative to conventional approaches.